The Transmission of Monetary Policy through Conventional and Islamic Banks - Sajjad Zaheer; Steven Ongena; Sweder van Wijnbergen (Tinbergen Institute, 2012)
We investigate the differences in banks' responses to monetary policy shocks across bank size, liquidity, and type, i.e., conventional versus Islamic, in Pakistan between 2002:II to 2010:I. We find that following a monetary contraction, small banks with liquid balance sheets cut their lending less than other small banks. In contrast large banks maintain their lending irrespective of their liquidity positions. Islamic banks, though similar in size to small banks, respond to monetary policy shocks as large banks. Hence ceteris paribus the credit channel of monetary policy may weaken when Islamic banking grows in relative importance.
urn:nbn:nl:ui:29-442095
Keywords: E5; G2; 330; Monetary policy; Islamic Banking; Pakistan; Geldpolitik; Geldpolitische Transmission; Bankenliquidität; Islamisches Finanzsystem; Pakistan